PERSEPSI PETANI TERHADAP PEMANFAATAN BANTUAN COMBINE HARVESTER DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Mohamad Riyan Suganda; Kardiana K Rangga; Indah Listiana (JURNAL AGRIBISNIS TERPADU, 2020)
The purposes of this research are to analyze rice farmer’s perception in use of  giving Combine harvester in Gadingrejo subdistrct, Pringsewu Regency. This research was conducted in Gadingrejo subdistrict, Pringsewu regency with 88 respondents of rice farmer’s group members were giving Combine harvester . Data were collected using a suvey method with descriptive analysis. The results showed that active rice farmer’s perception group members farmer’s of relative advatage, compatibility, complexity, triabilitiy, dan obsevabiliti in use of  giving Combine harvester included in the positif calssification. Perceptions rice farmer’s group members are not active of relative advantage inculude in quite well and perceptions of compatibility, complexity, triabilitiy, dan obsevabiliti in use of  giving Combine harvester included in the negative calssification.